Menyoal Kinerja KPK: Antara Harapan dan Pencapaian - Ramadhana, Kurnia (Integritas : Jurnal Antikorupsi, 2019)
The leadership of the Corruption Eradication Commission will change soon. Based on Act Number 19 of 2009 about the Corruption Eradication Commission the term of office of five leaders of the anti-corruption institution is limited to only four years. On that basis, the following article will discuss the Corruption Eradication Commission during the 2016-2018 period. the focus of this study is divided into two parts, namely the performance of the KPK in court and the ability of the KPK leadership to manage safety. For the trial section the author tries to analyze: 1) Using the rules of money laundering in each indictment; 2) Average prison charge; 3) Trend of revocation of political right. Then, in the institutional context, the highlights are some of the problems that occurred during the era of leadership volume IV and internal ethical enforcement in the KPK. In fact, there are still many crucial records over the past few years that should be considered by the next leadership terms.